Analysis of Output Costs Standard in The Framework of Performance-Based Budgeting - Hanafi Hari; Luki Karunia; Neneng Sri Rahayu (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to formulate the Special Output Cost Standards for the Deputy for Prevention and Monitoring of the Corruption Eradication Commission (CEC). The Special Output Cost Standards calculations are carried out using the Activity Based Costing (ABC) approach. This method is used because it is activity-based so it can be applied to public organizations and the values are more accurate. This study applies a qualitative descriptive method to explain the object of research qualitatively. Data were collected in three ways: interviews, observation, and document analysis. The locus of research is the Deputy for Prevention and Monitoring of the CEC, because it does not yet have a Special Output Cost Standards and the type of output can represent the duties of the CEC. The ABC method requires an analysis of business processes in order to effectively identify the activities required in achieving the output. The resulting Special Output Cost Standards is expected to be the best cost standard that can be implemented. The results of research on activities within the Deputy for Prevention and Monitoring found 4 outputs whose cost calculations have a little difference between the calculations of the ABC method and the realization of the previous 3 years, namely Registration of LHKPN, Examination of LHKPN, Determination of Gratuity Status and Carrying Out of The Study. These four outputs can be interpreted as having activities that tend to be the same each year, so it is necessary to propose their stipulation as Special Output Cost Standards.